Knowledge level of Hybrid Rice among farmers in Balaghat district - Pavan Kumar Rahangdale, D. K. Bose and Chandni Patle, (Indian Journal of Extension Education, 2018)
The present investigation entitled “a study on knowledge about hybrid rice production technology among the farmer inBalaghat District of Madhya Pradesh” was carried out in purposively selected four blocks of to assess the knowledgeabout hybrid rice growers. A total of 320 hybrid rice growers were selected randomly and data were collected throughpersonal interview schedule. The collected data were tabulated and analyzed statistically to draw appropriate conclusions.The study revealed that majority of the respondents (53.75%) were found in middle age group and educated up to primarylevel (25.62%) having medium size of family(59.38%). Majority of the respondents (66.25%) had medium experience ofhybrid rice cultivation. Maximum number of the respondents (49.37%) having medium size of land holdings (2.1 to 4 ha)and have annual income between Rs. 20,001 to Rs. 40,000. Majority of the respondents (61.90%) were also obtained shortterm credit from co-operative societies